Heliantheae s.l. (Asteraceae) nas serras do Cabral e do Caraça, Minas Gerais, Brasil - Bueno, Vinicius Resende (2018)
Systematic treatments of Heliantheae s.l. were done for the “Serra do Cabral” and “Serra do Caraça”, which are located in the central portion of the Espinhaço Range and in “Quadrilátero Ferrífero), respectively. It was found 34 species for the Serra do Cabral and 14 species for Caraça, only two shared for the Serras. The genera with highest number os species in both area were Aspilia Thouars and Calea L., and to the Serra do Cabral can also highlight genus Aldama La Llave & Lex. There was the first record of Aldama amphichlora (S.F.Baker) E.E.Schill. & Panero to Minas Gerais, and also of Aspilia caudata J.U.Santos in the Serra do Caraça, a threatened species. Are described two new species belonging to the genera Aspilia, and Dimerostemma Cass.. For each systematic treatment is presented an identification key, descriptions, taxonomic comments, notes about the time of flowering and on the geographical distribution of species.